Gestational headaches: characteristics and influencing factors in South-Western Nigeria - Adebayo, Philip Babatunde; Tijani, Aramide Mikhail; Abayomi, Olukayode; Akintunde, Adeseye Abiodun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Headache is one of the common neurological diseases in pregnancy but its pattern and influencing factors are yet to be determined in our environment in Nigeria. The aim of this study was to determine the prevalence and characteristics, as well as the modifying factors for gestational headaches in Ogbomoşo, Nigeria. Methods: This study was a bi-institutional cross-sectional descriptive study. Three hundred and eight (308) eligible pregnant women attending the ante-natal care of the Ladoke Akintola University of Technology and Ogbomoso South local government hospitals in Ogbomoso were recruited consecutively, between November10, 2012 and February 28, 2013. Using an interviewer administered questionnaire, socio-demographic, obstetrics and headache related variables were obtained from eligible pregnant women. Gestational headaches were characterized using the international classification of headache disorders II (ICHD-II). The prevalence of migraine and tension type headache were determined before and during pregnancy. Improvement rates (defined by reduced headache frequency and severity) were determined. Results: The prevalence of Headaches before and during pregnancy was 25% and 23.3% respectively (P = 0.661).Migraine prevalence was 8.4% and 5.5% before and during pregnancy respectively (P = 0.34); while the prevalence of Tension-Type Headaches (TTH) was 16.5% and 17.9% before and during pregnancy (P = 0.63). Improvement rate was 100% for migraine and 85.5% for TTH. Multiple logistic regressions revealed that poor personal income, unemployment and multi-parity were predictive factors for headaches in pregnancy. Conclusions: Migraine and Tension type headaches were prevalent in this population and they are worsened by poor personal income, unemployment and multi-parity. Interventions and programs to subsidize antenatal care may prevent gestational headaches in this population.